Three-Year Study of Markers of Oxidative Stress in Exhaled Breath Condensate in Workers Producing Nanocomposites, Extended by Plasma and Urine Analysis in Last Two Years - Daniela Pelclova; Vladimir Zdimal; Martin Komarc; Jaroslav Schwarz; Jakub Ondracek; Lucie Ondrackova; Martin Kostejn; Stepanka Vlckova; Zdenka Fenclova; Stepanka Dvorackova; Lucie Lischkova; Pavlina Klusackova; et al. (Nanomaterials, 2020)
Human data concerning exposure to nanoparticles are very limited, and biomarkers for monitoring exposure are urgently needed. In a follow-up of a 2016 study in a nanocomposites plant, in which only exhaled breath condensate (EBC) was examined, eight markers of oxidative stress were analyzed in three bodily fluids, i.e., EBC, plasma and urine, in both pre-shift and post-shift samples in 2017 and 2018. Aerosol exposures were monitored. Mass concentration in 2017 was 0.351 mg/m3 during machining, and 0.179 and 0.217 mg/m3 during machining and welding, respectively, in 2018. In number concentrations, nanoparticles formed 96%, 90% and 59%, respectively. In both years, pre-shift elevations of 50.0% in EBC, 37.5% in plasma and 6.25% in urine biomarkers were observed. Post-shift elevation reached 62.5% in EBC, 68.8% in plasma and 18.8% in urine samples. The same trend was observed in all biological fluids. Individual factors were responsible for the elevation of control subjects’ afternoon vs. morning markers in 2018; all were significantly lower compared to those of workers. Malondialdehyde levels were always acutely shifted, and 8-hydroxy-2-deoxyguanosine levels best showed chronic exposure effect. EBC and plasma analysis appear to be the ideal fluids for bio-monitoring of oxidative stress arising from engineered nanomaterials. Potential late effects need to be targeted and prevented, as there is a similarity of EBC findings in patients with silicosis and asbestosis.